2014
DOI: 10.1371/journal.pone.0102645
|View full text |Cite
|
Sign up to set email alerts
|

The South Asian Genome

Abstract: The genetic sequence variation of people from the Indian subcontinent who comprise one-quarter of the world's population, is not well described. We carried out whole genome sequencing of 168 South Asians, along with whole-exome sequencing of 147 South Asians to provide deeper characterisation of coding regions. We identify 12,962,155 autosomal sequence variants, including 2,946,861 new SNPs and 312,738 novel indels. This catalogue of SNPs and indels amongst South Asians provides the first comprehensive map of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 47 publications
(51 reference statements)
3
47
0
Order By: Relevance
“…The association between PNPLA3 variants and elevated ALT in the general population [7][8][9], or in patients with steatosis assessed by proton magnetic resonance spectroscopy [10], was also reported by various other teams. Interestingly, Sookoian et al replicated the findings of Romeo et al [6] in NAFLD and extended the association to histological severity, including nonalcoholic steatohepatitis (NASH), after adjustment for age, sex, BMI, and insulin resistance [11].…”
Section: Nonalcoholic Fatty Liver Diseasesupporting
confidence: 55%
“…The association between PNPLA3 variants and elevated ALT in the general population [7][8][9], or in patients with steatosis assessed by proton magnetic resonance spectroscopy [10], was also reported by various other teams. Interestingly, Sookoian et al replicated the findings of Romeo et al [6] in NAFLD and extended the association to histological severity, including nonalcoholic steatohepatitis (NASH), after adjustment for age, sex, BMI, and insulin resistance [11].…”
Section: Nonalcoholic Fatty Liver Diseasesupporting
confidence: 55%
“…95,96 Many of these studies were conducted in individuals of primarily European decent, however there is emerging evidence of susceptible genes impacting CVD risk in SA. 97 In the EpiDREAM study, 16 SNP were associated with increased CVD risk in Europeans, SA and Latinos at risk of DM. On average, SA had a greater genetic load of SNPs associated with DM risk, yet had a similar degree of association for each SNP, implying that SA had a greater population attributable risk of genetic variants associated with DM.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Information from this study will hopefully accelerate the identification of genetic variants associated with CVD in SA. 97 A unifying genetic theory explaining a shared predisposition to DM, adipose tissue gain and related CVD risk is the "thrifty gene" hypothesis. If SA evolved during times of resource scarcity, a beneficial phenotype would retain excess nutrients.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…QTLs for anticoagulants such as protein C and protein S were also reported [14,15]. A recent study reported on the identification of genetic loci associated with the plasma concentrations of liver enzymes [16].…”
Section: Resultsmentioning
confidence: 99%